Carbon nanoparticle modified screen printed carbon electrode as a disposable electrochemical immunosensor strip for the detection of Japanese encephalitis virus - Suk, Fun Chin; Lih, Shan Lim; Suh, Cem Pang; Magdline Sia, Henry Sum; David, Perera (Springer-Verlag, 2017)
The authors describe a disposable electrochemical immunosensor strip for the detection of the Japanese encephalitis virus (JEV). The assay is based on the use of a screen printed carbon electrode (SPCE) modified with carbon nanoparticles (CNPs) that were prepared from starch nanoparticles and deposited on the SPCE working electrode whose surface was functionalized with 3-aminopropyl triethoxysilane. Next, antibody of JEV was immobilized on the surfaces of the CNPs. The analytical performance of immunosensor strip was characterized using cyclic voltammetry (with hexacyanoferrate as the redox probe) and electrochemical impedance spectroscopy. The deposition of CNPs enhances the electron transfer kinetics and current intensity of the SPCE by 63% compared to an unmodified SPCE. Under optimized conditions, the calibration plot is linear within the 5–20 ng·mL−1 JEV concentration range, the limit of detection being 2 ng·mL−1 (at an S/N ratio of 3), and the assay time is 20 min. This immunosensor strip was successfully applied to the detection of JEV in human serum samples. It represents a cost-effective alternative to conventional diagnostic tests for JEV.